2020
DOI: 10.21203/rs.3.rs-101517/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on miRNAs-Mediated Seed and Stone-Hardening Regulatory Networks and the Mechanism of miRNAs’ Manipulating Gibberellin-Induced Seedless Berries in Grapevine (Vitis vinifera L.)

Abstract: A significant body of evidence supports the important roles of miRNAs in grape berry developments. However, their specific molecular functions during stone-hardening stage development remain unclear. Here, a total of 161 conserved and 85 species-specific miRNAs/miRNAs*(precursor) were identified in grape stone hardening stage berries using Solexa sequencing. Out of them, 30 VvmiRNAs were tissue-specific and identified as stone-hardening related to VvmiRNAs, whereas 52 exhibited differential expression profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Various studies have indicated that the expression level of miR395a is different significantly in developing fruit such as the seeds of Siberian apricot [ 17 ], pear fruit [ 18 ] and common bean seed [ 57 ]. Also, identification of known miR395 family in the stone-hardening stage of grape berries showed that involved in grape development and ripening process [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have indicated that the expression level of miR395a is different significantly in developing fruit such as the seeds of Siberian apricot [ 17 ], pear fruit [ 18 ] and common bean seed [ 57 ]. Also, identification of known miR395 family in the stone-hardening stage of grape berries showed that involved in grape development and ripening process [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dhaka and Sharma [ 25 ] identified 21 different miRNAs experimentally to regulate seed size, nutritional content, vigor, and shattering. Moreover, high throughput sequencing has been recently used for the identification and expression profiling of miRNAs in many fruit crops, such as sweet orange [ 26 ], grape [ 27 ], papaya [ 28 ], strawberry [ 29 , 30 ], olive [ 31 ], banana [ 32 ] and Grapevine [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of the PbGA20ox2 gene modified the GA biosynthetic pathway and improved GA4 synthesis, which promoted fruit set and parthenocarpic fruit improvement in pear fruits (Pyrus Bretschneider Rehd.) (Wang et al, 2020a). The PpIAA19 gene used to be concerned in the regulation of lateral root number, stem elongation, parthenocarpy, and fruit structure of tomatoes (Ding et al, 2019) and grapevines (Wang et al, 2020a).…”
Section: Seedless Fruit Development (Parthenocarpy)mentioning
confidence: 99%
“…(Wang et al, 2020a). The PpIAA19 gene used to be concerned in the regulation of lateral root number, stem elongation, parthenocarpy, and fruit structure of tomatoes (Ding et al, 2019) and grapevines (Wang et al, 2020a). The overexpression of the MaTPD1A gene in banana plants produces seedless fruits in contrast to wild-type plants (Hu et al, 2020).…”
Section: Seedless Fruit Development (Parthenocarpy)mentioning
confidence: 99%